Role of dietary lipid in growth and disease resistance of hybrid lemon fin barb larvae (Hypsibarbus wetmorei Smith 1931 ♂×Barbonymus gonionotus Bleeker 1849 ♀) - Weerasingha, Rochana (2022)
Most carp larvae including hybrid lemon fin barb readily accept formulated microdiets at first feeding. Dietary protein and energy requirements for this larval hybrid, a cross of Hypsibarbus wetmorei male and Barbonymus gonionotus female, have been reported. This study focused on determining its lipid requirements including the best lipid source and the requirements for phospholipids and cholesterol. In Experiment 1, three days old larvae were randomly stocked at 10 larvae L-1 in fifteen 9 L tanks and fed the test diets containing 0, 4, 8, 12 and 16 % cod liver oil for 20 days four times a day. The larvae fed elevated dietary lipid levels exhibited higher (p<0.05) survival and growth compared to those fed a lipid-free diet. Excessive dietary lipid levels (>13.5%) reduced the larval growth and increased lipid droplets in the liver and intestine indicating a 13.5% optimum dietary lipid level for maximum growth. In Experiment 2 and the following experiments, larvae were stocked at the rate of 50 larvae L-1 in fifteen 5 L tanks. Cod liver oil was replaced with crude palm oil at 0, 25, 50, 75 and 100 %. Dietary replacement of cod liver oil did not affect (p>0.05) survival and growth of hybrid larvae. Lipid vacuoles were observed in the liver and intestine of larvae fed 0, 25 and 100 % crude palm oil when challenged with Aeromonas hydrophila. Five plant oils were evaluated in Experiment 3. The survival of larvae fed crude palm oil was significantly higher (p<0.05) than those fed linseed oil, canola oil and soybean oil. The growth of larvae fed crude palm oil and linseed oil diets was significantly higher (p<0.05) than that of larvae fed with soybean oil. Isolipidic diets containing 0, 1, 2, 4 and 6 % soy lecithin were tested in Experiment 4. While the survival was not affected, the weight gain and protein efficiency ratio (PER) of hybrid larvae fed 4% soy lecithin were significantly higher (p<0.05) than those of larvae fed 0-2 % soy lecithin. Lipid vacuoles decreased in the liver and gut of hybrid larvae fed 2 and 4 % dietary phospholipid when challenged against A. hydrophila. The recommended dietary phospholipid level for the hybrid larvae was 4%. In Experiment 5, five isolipidic diets containing 0, 0.5, 1, 1.5 and 2 % cholesterol with 4% phospholipid were tested. Elevated dietary cholesterol levels did not affect the survival and growth of hybrid larvae but increased lipid vacuoles in their liver and gut. Disease resistance against A. hydrophila decreased with the inclusion of dietary cholesterol. In conclusion, hybrid lemon fin barb larvae required 13.5% lipid, includes 4% phospholipid. Dietary cholesterol did not improve larval disease resistance and their survival and growth. Crude palm oil was the best plant oil that could fully replace fish oil in hybrid larval diets.